(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Determine factors asccoiated with dementia in elderly in Nghe An Province (2022-2023) Method: Designed descriptive research method Results:Analyzing factors asccoiated with dementia include: diabetes, hypertension, overweightobesity, total blood cholesterol, LDL-Cholesterol, Triglycerides, blood glucose, education level counseling, participation in social activities, physical activities, recreational activities, nutrition level, alcohol use, smoking... Results: the asccoiated factors include: high blood pressure (OR = 1.657; 95% CI from 1.122-2.446; p < 0.05); drug use (OR = 2.057; 95%CI from 1.217-3.476; p < 0.05); sleep disorders (OR = 1.735; 95%CI from 1.161-2.593; p < 0.05); lack of participation in physical activity (OR = 1.725; 95%CI from 1.134-2.625; p < 0.05); lack of participation in recreational activities (OR = 2.038; 95%CI from 1.315-3.157; p < 0.05); Education level below high school (OR = 2.953; 95%CI from 1.347-6.477; p < 0.05); age bracket 75-79 (OR = 3.201; 95%CI from 1.274-8.040; p < 0.05); age bracket 80-84 (OR = 3.549; 95%CI from 1.447-8.701; p < 0.05); age bracket 85-89 (OR = 4.885; 95%CI from 1.988- 12.003; p < 0.05); age bracket ≥ 90 (OR = 7.729; 95%CI from 2,987-20,000; p < 0.05). Conclusion: Factors asccoiated with dementia are: high blood pressure, smoking, sleep disorders, lack of participation in physical activities, lack of participation in recreational activities, age group, low education level.